2014
DOI: 10.1071/sr14049
|View full text |Cite
|
Sign up to set email alerts
|

Soil fertility changes following conversion of grassland to oil palm

Abstract: Impacts of palm oil industry expansion on biodiversity and greenhouse gas emissions might be mitigated if future plantings replace grassland rather than forest. However, the trajectory of soil fertility following planting of oil palm on grasslands is unknown. We assessed the changes in fertility of sandy volcanic ash soils (0–0.15 m depth) in the first 25 years following conversion of grassland to oil palm in smallholder blocks in Papua New Guinea, using a paired-site approach (nine sites). There were signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 22 publications
0
10
1
Order By: Relevance
“…A similar finding was reported by Guillaume et al (2016), who attributed the high soil degradation under oil palm plantations to management strategies adopted especially in interrow. In addition, Nelson et al (2014) reported a significant decline in soil fertility following the conversion of grassland to oil palm plantation. The variation in soil fertility distribution may be related to differences in nutrient cycling mechanism under varying vegetation types.…”
Section: Spatial Pattern Of Sfi Under Rainforest and Tree Plantationsmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar finding was reported by Guillaume et al (2016), who attributed the high soil degradation under oil palm plantations to management strategies adopted especially in interrow. In addition, Nelson et al (2014) reported a significant decline in soil fertility following the conversion of grassland to oil palm plantation. The variation in soil fertility distribution may be related to differences in nutrient cycling mechanism under varying vegetation types.…”
Section: Spatial Pattern Of Sfi Under Rainforest and Tree Plantationsmentioning
confidence: 99%
“…In addition, the high leaf fall may provide soil cover, which may reduce erosion and leaching in rubber plantations (Guillaume et al, 2016). Soil fertility in oil palm plantation has been known to improve under frond piles while it reduces in other zones (Nelson et al, 2014).…”
Section: Spatial Pattern Of Sfi Under Rainforest and Tree Plantationsmentioning
confidence: 99%
“…Where oil palm and rubber plantations or even pasture lands become flooded, CH 4 emissions increase because methanogens utilize labile C substrates under anaerobic conditions, resulting in CH 4 production [61,63,[69][70][71]; this is generally related to soil fertility [72]. CO 2 emissions from soil, calculated from net SOC changes (primarily from heterotrophic respiration), varied between 1 t/ha/year (from grassland to oil palm plantation) and 5.5 t/ha/year (from slash-burn agriculture to oil palm plantation) ( Table 2) [42,[73][74][75][76][77][78][79][80][81]. Land use change from secondary forest to oil palm and degraded grassland to young rubber tree plantation may even create a soil CO 2 sink (2-3.7 t/ha/year), although only limited data are available at this stage to support this claim for young rubber plantations.…”
Section: Effect Of Different Land Uses On Ghg Fluxes From Tropical MImentioning
confidence: 99%
“…For example, adding crop residues can increase SOC and soil fertility, and improve degraded savanna soils (Rhebergen et al, 2020 ; Tao et al, 2016 , 2017 ). Fine‐scale spatial differences in soil properties are common in OP plantations due to the distribution of litter and other crop residue inputs as well as fertilizer within plantations (Nelson et al, 2014 ; Rüegg et al, 2019 ). This non‐random distribution of nutrient resources within plantations should be considered when assessments of soil properties and processes are attempted (Goodrick et al, 2016 ; Nelson et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%